The Influence of Basic Accounting Courses, Introduction to Information Technology and English on Accounting Computer Skills - Iskandar, Muh. Iskandar Sabang (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2025)
This study aims to determine the determinants that affect the ability of accounting students in the Computer Accounting course. The determinants are the basic accounting courses, Introduction to Information Technology, and English. This research method is a type of quantitative research that takes a saturated sample at the score of 618 accounting students who have taken computer accounting courses and is processed using Microsoft Excel data analysis tools. The results show that the scores obtained by students in the Basic Accounting, Introduction to Information Technology, and English courses have a positive and significant effect on the grades or abilities in the Computer Accounting course.